Gendered impacts of climate-smart agriculture on household food security and labor migration: insights from Bihar, India - Agarwal, Tripati; Goel, Prarthna A; Gartaula, Hom Nath; Rai, Munmun; Bijarniya, Deepak; Rahut, Dil B; Jat, Mangi L (Emerald Publishing Limited, 2022)
Increasing trends of climatic risk pose challenges to the food security and livelihoods of smallholders in vulnerable regions, where farmers often face loss of the entire crop, pushing farmers (mostly men) out of agriculture in destitution, creating a situation of agricultural making agriculture highly feminization and compelling male farmers to out-migrate. Climate-smart agricultural practices (CSAPs) are promoted to cope with climatic risks. This study aims to assess how knowledge related to CSAPs, male out-migration, education and income contribute to the determinants of male out-migration and CSAPs adoption and how they respond to household food security.